2013
DOI: 10.1080/10807039.2012.708292
|View full text |Cite
|
Sign up to set email alerts
|

Human Health Risk Assessment of a Civilian-Accessible Active Firing Range

Abstract: The Korean Federation of Teachers Association, the Korea Ministry of Education, Science and Technology, and the Korea Ministry of National Defense (KMND) concluded a memorandum of understanding (MOU) on opening military sites to elementary, middle, and high school students to strengthen national security consciousness. According to the MOU, the KMND decided to open an active firing range; however, due to the ongoing firing activity, site contamination by toxic energetic materials (EMs) was suspected. To identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…2,4,6‐T rinitrotoluene (TNT) and hexahydro‐1,3,5‐trinitro‐1,3,5‐triazine (RDX) are nitro explosives that are not easily degradable under environmental conditions and are toxic to microbes, algae, fish, and other organisms, including humans (Won et al, 1976; Yinon, 1990; Harvey et al, 1991). It has been reported that soil and groundwater in the proximity of shooting and artillery ranges, proving grounds, and munitions‐manufacturing plants are often contaminated with these explosives (Hundal et al, 1997; Boopathy and Manning, 2000; Certini et al, 2013; Jung et al, 2013). Because of their toxicity, immediate remediation actions are needed to prevent dispersion of nitro explosives in natural water and soil.…”
mentioning
confidence: 99%
“…2,4,6‐T rinitrotoluene (TNT) and hexahydro‐1,3,5‐trinitro‐1,3,5‐triazine (RDX) are nitro explosives that are not easily degradable under environmental conditions and are toxic to microbes, algae, fish, and other organisms, including humans (Won et al, 1976; Yinon, 1990; Harvey et al, 1991). It has been reported that soil and groundwater in the proximity of shooting and artillery ranges, proving grounds, and munitions‐manufacturing plants are often contaminated with these explosives (Hundal et al, 1997; Boopathy and Manning, 2000; Certini et al, 2013; Jung et al, 2013). Because of their toxicity, immediate remediation actions are needed to prevent dispersion of nitro explosives in natural water and soil.…”
mentioning
confidence: 99%
“…Intertwined components of the full risk assessment framework employed in the literature, including the evaluation of military-impacted sites, are summarized in Figure 3. The majority of the reviewed studies from earlier dates include Level 1 activities along with some of the Level 2 activities, e.g., consideration of site-specific soil characterization and selection of reference values ( Figure 3); only a few publications utilizing a complete risk characterization and assessment including the activities in Levels 1 to 3 are present [6,101]. Risks to neonatal or reproductive health from PTEs may require partially different approaches than this framework.…”
Section: Risk Assessment Of Military-impacted Sitesmentioning
confidence: 99%
“…Thus, it was concluded from the risk assessment that there is an immediate need for remediation of both carcinogens and non-carcinogens before construction of a reservoir. Jung et al [101] assessed human health risks from an open firing range in Korea for civilians during their site visit. TNT, RDX, HMX, and 2-ADNT were selected as the contaminants for the risk assessment.…”
Section: Risk Assessment Of Military-impacted Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,6‐trinitrotoluene (TNT) and hexahydro‐1,3,5‐trinitro‐1,3,5‐triazine (RDX) are the most widely used explosives in the world and are known to be toxic to microbes, algae, fish, and other organisms . It has been reported that soil and groundwater in the vicinity of shooting ranges, proving grounds, and munitions‐manufacturing plants are often contaminated with these explosives . Conventionally, explosives in a natural environment have been treated through costly open burning/open detonation (OP/OD).…”
Section: Introductionmentioning
confidence: 99%